Case report: Suicide and inhibitions of thinking—An integrative view from traditional psychoanalytic and mentalizing perspectives - Seng Choi, Chong (Frontiers in Psychiatry, 2023)
Suicide has been the subject of exploration in psychoanalysis. From Freud's internalized aggression and self-objectification in melancholic depression to contributions from object relation and self-psychology theorists, several of these central clinical concepts seem to share the commonality that one encounters an inhibition of thinking in a suicidal state of mind. Their freedom of thought is inhibited unswervingly despite the notion that we are born to think. Most psychopathologies, including suicide, relate to how we are often stuck with our thoughts. Thinking beyond this sense comes with significant emotional resistance. This case report follows through an attempt to integrate the hypothesized inhibitions on one's capability to think, involving one's own core conflicts and dysfunctional mental processing from the traditional psychoanalytic and mentalizing perspectives. The author hopes that further conceptualizations and research will empirically investigate these assumptions, potentially improving suicide risk assessment and prevention and enhancing psychotherapeutic outcomes.